KNOWLEDGE OF SLUM COMMUNITY TOWARD LEPROSY: A CROSS-SECTIONAL SURVEY FROM KARAD URBAN BLOCK OF WESTERN MAHARASHTRA, INDIA - Mohite, Rajsinh Vishwasrao (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The objectives of this study are to assess the knowledge of urban slum community toward leprosy and to determine the relationship between sociodemographic variables and knowledge about leprosy. Methods: The study was planned during September 2016 to October 2016, as a community-based cross-sectional survey conducted at Karad urban slum area of state Maharashtra, India. The sample size calculated was a total of 246 slum community members, aged 20â€“60 years, enrolled randomly and interviewed by utilizing pre-tested structured pro forma. Data collected were analyzed and presented in tabular form. Chi-square test was used to determine the association between study variables. Results: A total of 246 respondents were interviewed of which maximum 42.2% were in the age group 30â€“40 years. The problem of illiteracy was 25.6% and maximum 67.4% were engaged in daily wage labor force. The overall knowledge about leprosy was poor responded by more than half (55.6%) of the study participants. Maximum, 78% slum dwellers knew about leprosy disease, whereas their knowledge about the cause of disease, sign, and symptoms, infectivity and curability was around 50%. Maximum 68% of participants responded that disease is confined to poor people. The age, education, and occupational status of slum dwellers were significantly associated with knowledge about leprosy. Conclusion: The present study concluded that poor knowledge of slum community toward leprosy could be an important determinant of poor performance of the National Leprosy Eradication Programme at urban community.